Dosimetric accuracy of a treatment planning system for actively scanned proton beams and small target volumes: Monte Carlo and experimental validation. (24th August 2015) - Magro, G; Molinelli, S; Mairani, A; Mirandola, A; Panizza, D; Russo, S; Ferrari, A; Valvo, F; Fossati, P; Ciocca, M
Abstract: This study was performed to evaluate the accuracy of a commercial treatment planning system (TPS), in optimising proton pencil beam dose distributions for small targets of different sizes (5–30 mm side) located at increasing depths in water. The TPS analytical algorithm was benchmarked against experimental data and the FLUKA Monte Carlo (MC) code, previously validated for the selected beam-line. We tested the Siemens syngo ® TPS plan optimisation module for water cubes fixing the configurable parameters at clinical standards, with homogeneous target coverage to a 2 Gy (RBE) dose prescription as unique goal. Plans were delivered and the dose at each volume centre was measured in water with a calibrated PTW Advanced Markus ® chamber. An EBT3 ® film was also positioned at the phantom entrance window for the acquisition of 2D dose maps. Discrepancies between TPS calculated and MC simulated values were mainly due to the different lateral spread modeling and resulted in being related to the field-to-spot size ratio. The accuracy of the TPS was proved to be clinically acceptable in all cases but very small and shallow volumes. In this contest, the use of MC to validate TPS results proved to be a reliable procedure for pre-treatment plan verification.